COMBATING INFODEMIC COVID-19: GOVERNMENT RESPONSE AGAINST FAKE NEWS ON SOCIAL MEDIA - Andi Luhur Prianto; Abdillah Abdillah; Syukri Syukri; Firdaus Muhammad; Arifeen Yama (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
The global commitment to fighting the pandemic is not only about medical and epidemiological work, but also about how information about the disease is disseminated. The threat of the Covid-19 infodemic is no less dangerous than the pandemic itself. The phenomenon of infodemic has distorted the work of science and reduced public trust in state authorities. This research has identified, mapped, and analyzed official government responses to fake news attacks on social media. This study uses an interpretive-phenomenological approach, related to the spread and belief of fake news about Covid-19 in Indonesia. Data analysis uses the Nvivo-12 Pro application, as an artificial intelligence tool to support data exploration from various sources. The results show that the quality of media literacy, public communication performance, and the effectiveness of government regulations have become part of the challenges in mitigating infodemic. The level of public trust in information from social media contributes to the decline in trust in fake news about Covid-19. Stimulation from the social media news that does not control the belief in myths and false information about Covid-19. Content creators who have produced, posted, and shared on social media channels that are less critical, have an impact on the infodemic situation. The solution is to increase media literacy education and the effectiveness of law enforcement in mitigating the infodemic in Indonesia.